Asian Development Bank Japan scholarship program annual report 2017. (Asian Development Bank, 2019)
This publication presents the activities, achievements, and success stories of students and alumni from the Japan Scholarship Program in 2017.The program gives qualified citizens from ADB developing member countries an opportunity to take postgraduate studies in economics, business and management, science and technology, and other development related fields at 29 educational institutions in Asia and the Pacific. Between 1988 and 2017, Japan contributed 178 dollar million to the program. Since 1988, a total of 3,660 scholarships have been awarded to recipients including 1,382 women from 37 countries. Of the total, 3,303 scholars have completed their courses. An average of 143 scholarships are awarded each year.